2018
DOI: 10.1111/bjir.12434
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Occupational Licensing: Evidence from Business‐Level Data

Abstract: Occupational licensing currently affects more than 1,000 occupations in the United States. I use confidential US Census Bureau business micro-data to shed light on the effect of occupational licensing in cosmetology on key market outcomes and study its effect on the providers of occupational training. Occupational licensing regulation does not seem to affect the equilibrium number of practitioners or prices of services to consumers, but is associated with significantly lower practitioner entry and exit rates. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…This study shifts the focus away from consumers and employees and toward how occupational licensing affects business decisions. Zapletal (2018) is the closest study to my own, as it focuses on the location decisions of businesses, though it focuses specifically on personal-care industries. Zapletal finds that the restrictiveness of licensure affects businesses' decisions to enter and exit but not the overall quality or prices of their cosmetology services.…”
Section: Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…This study shifts the focus away from consumers and employees and toward how occupational licensing affects business decisions. Zapletal (2018) is the closest study to my own, as it focuses on the location decisions of businesses, though it focuses specifically on personal-care industries. Zapletal finds that the restrictiveness of licensure affects businesses' decisions to enter and exit but not the overall quality or prices of their cosmetology services.…”
Section: Literaturementioning
confidence: 99%
“…Previous studies have focused on the effects of occupational licensing on employees in the form of wage premiums and on consumers in the form of changes in the price and quality of goods and services, but few studies have investigated the aggregated or disaggregated effects of costs on firm decision-making. This work seeks to complement similar work by Zapletal (2018), in which he looked at the entry and exit of cosmetology, by abstracting to observe the aggregate effects on overall firm behaviour across all industries. While aggregation is necessary with firm-level data to measure the response of firm to the regulatory environment, attempts at disaggregation are also provided for specific case studies to ensure to trend is consistent when replicating an industry-focused approach.…”
Section: Introductionmentioning
confidence: 99%
“…A principal function of private sector unions is to reallocate economic surplus from capital to labor, as we discussed. By contrast, an occupational licensing requirement reallocates surplus from consumers, licensure applicants, and unlicensed workers to licensed workers and training providers (Nunn 2018; Zapletal 2019; Kleiner and Soltas 2019).…”
Section: How Labor Market Institutions Affect Workersmentioning
confidence: 99%
“…In terms of laborers, workers who are subject to an occupational license often benefit from wage premiums within many industries; however, some studies have found that these licenses have also reduced aggregate economic and geographic mobility (Timmons and Thornton, 2008; Perloff, 1980; Guis, 2016; Kleiner and Park, 2010; Kleiner and Krueger, 2010, 2013; Meehan et al , 2019). In areas and industries with these wage premiums, there is also evidence of reduction in labor supply entry (Thornton and Weintraub, 1979; Hall and Pokharel, 2016; Zapletal, 2018). These wage premiums are thought to represent the additional cost of education and training, incentivize public health and safety and increase overall quality of goods and services (Akerlof, 1970; Shapiro, 1986).…”
Section: Literature Reviewmentioning
confidence: 99%